The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00421-010-1782-2
|View full text |Cite
|
Sign up to set email alerts
|

Postural ability reflects the athletic skill level of surfers

Abstract: This work analyses surfers' postural control and their use of visual information in static (stable) and dynamic (unstable) postures according to their level of competition. Two groups of healthy surfers were investigated: a group of local level surfers (LOC) (n = 8) and a group of national/international level surfers (NIN) (n = 9). Posture was assessed by measuring the centre of foot pressure with a force platform for 50 s with stable support and for 25 s with unstable support (sagittal or frontal plane). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 17 publications
(25 reference statements)
8
61
1
2
Order By: Relevance
“…While standing on a stable support, the athletes show less visual dependence and increased sway velocity, as compared to the non-athletes. The lesser visual dependence on the standing balance of athletes is in line with similar findings for the expert surfers (Paillard et al 2010) and 13-year-old soccer players (Bieć and Kuczyński 2010). To explain these and other results obtained from the standing balance of athletes, however, one must bear in mind that actually the athletes' sport practice is instrumented (e.g.…”
Section: Discussionsupporting
confidence: 61%
“…While standing on a stable support, the athletes show less visual dependence and increased sway velocity, as compared to the non-athletes. The lesser visual dependence on the standing balance of athletes is in line with similar findings for the expert surfers (Paillard et al 2010) and 13-year-old soccer players (Bieć and Kuczyński 2010). To explain these and other results obtained from the standing balance of athletes, however, one must bear in mind that actually the athletes' sport practice is instrumented (e.g.…”
Section: Discussionsupporting
confidence: 61%
“…Several studies have shown that increases in training intensity or training until exhaustion is accompanied by a decrease in motor ability and reduction of postural control. For these reasons higher values of VT may delay the onset of fatigue and preserve psychomotor skills therefore reducing errors (Guidetti, Franciosi, Gallotta, Emerenziani, & Baldari, 2011;MendezVillanueva, et al, 2005;Paillard, Margnes, Portet, & Breucq, 2011). Our study supported the fact that higher values of LT may delay fatigue and its effects on performance outcome.…”
Section: Discussionsupporting
confidence: 81%
“…Probably ES are able to delay the effects of fatigue therefore preserving the coordinative and motor skills essential to surfing and reducing the occurrence of errors that can lead to poor decisions that influence the outcome on competition (MendezVillanueva & Bishop, 2005). Accordingly, the exercise intensity or duration to fatigue has been shown to be accompanied by a reduction motor ability and psychomotor skills (Guidetti et al, 2011;Paillard et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…El control postural de la muestra evaluada, es muy similar al descrito en otras muestras de surfistas. De este modo la velocidad del CdP registrada en el presente estudio (7,3 mm/s), fue parecida a la registrada por Paillard et al (2011) (8 mm/s), y algo más alta que la informada por Frank et al (2009) (4 mm/s). Por otro lado, el área del centro de presión registrada en la presente muestra (68,1 mm 2 ), fue menor que la registrada por Paillard et al (125 mm 2 ).…”
Section: Discussionunclassified